Synthesis and Pharmacological Studies of Some Complexes of Eu(III) Ion with Schiff Bases of Sulphanilamide - Rajendran, G.; Faisal, S. (Asian Journal of Chemistry, 2016)
Synthesis and characterization of some complexes of Eu(III) ion with Schiff bases of sulphanilamide having the molecular formula [Eu(L)3(NO3)3], [Eu(L)3(NCS)3], [Eu(L)3(ClO4)2]ClO4 where L = 4[N-(4-dimethylaminobenzalidene)amino]benzene sulphonamide (DBAB), 4[N-(4'-methoxybenzalidene)amino]benzene sulphonamide (MBAB), 4[N-(4'-hydroxy-3'-methoxybenzalidene)amino]benzene sulphonamide (HMBAB) and 4[N-(furfuralidene)amino]benzene sulphonamide (FAB), have been reported. The antimicrobial activity and thermal stabilities of these complexes were also studied. All the complexes exhibited moderate antibacterial activity. The extent of activity depends on the nature of secondary coordinated ligands such as the oxoanions.